Preliminary assessment and prioritisation of demand management strategies for reducing train overcrowding - Mohd Mahudin, Nor Diana (UPM Press, 2018)
Train overcrowding has been associated with psychological stress, adverse health effects, negative behavioural reactions, and spillover effects. However, there is little agreement on the appropriate demand management strategies to deal with the increasing passenger numbers, especially on rail services in Malaysia. To begin addressing this issue, a preliminary study involving 13 participants (Male = 8; Female = 5) from an organisation under the Ministry of Transport, Malaysia focusing on demand management issues and transportation research and development activities was conducted. Participants ranked three sets of demand management strategies (i.e., pricing, service quality, and policy) based on their feasibility, effectiveness, and cost. Using Kendall’s coefficient of concordance (Kendall’s W), findings showed a relatively weak, but consistent agreement rate among participants across all strategies on their feasibility, effectiveness, and cost. In particular, high priority was placed on four strategies (i.e., free early bird incentives, discounted early bird or off-peak fares, increasing train frequency, and travel demand management programme), implying their potential applications for peak smoothing in Malaysian urban rail systems. The implications for practice and limitations of this study are discussed. It is suggested that the identified strategies should be targeted for intervention and evaluation to further refine our understanding of sustainable, effective, and cost-efficient ways in addressing current and future train overcrowding issues.